Heparins from porcine and bovine intestinal mucosa: Are they similar drugs? - Aquino, Rafael S.; Pereira, Mariana S.; Vairo, Bruno C.; Cinelli, Leonardo P.; Santos, Gustavo R. C.; Fonseca, Roberto J. C.; Mourão, Paulo A. S. (Thrombosis and Haemostasis, 2010)
Increasing reports of bleeding and peri- or post-operative blood dyscrasias in Brazil were possibly associated with the use of heparin from bovine instead of porcine intestine. These two pharmaceutical grade heparins were analysed for potential differences. NMR analyses confirmed that porcine heparin is composed of mainly trisulfated disaccharides →4-α-IdoA2S-1→4-α-GlcNS6S-1→. Heparin from bovine intestine is also composed of highly 2-sulfated α-iduronic acid residues, but the sulfation of the α-glucosamine units vary significantly: ~50% are 6-and N-disulfated, as in porcine heparin, while ~36% are 6-desulfated and ~14% N-acetylated. These heparins differ significantly in their effects on coagulation, thrombosis and bleeding. Bovine heparin acts mostly through factor Xa. Compared to porcine heparin on a weight basis, bovine heparin exhibited approximately half of the anticoagulant and antithrombotic effects, but similar effect on bleeding. These two heparins also differ in their protamine neutralisation curves. The doses of heparin from bovine intestine required for effective antithrombotic protection and the production of adverse bleeding effects are closer than those for porcine heparin. This observation may explain the increasing bleeding observed among Brazilian patients. Our results suggest that these two types of heparin are not equivalent drugs.
Keywords: Venous thrombosis; glycosaminoglycans; heparins; serpins; thrombosis